2018
DOI: 10.1063/1.5012984
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the various contributions to pyroelectricity in lead zirconate titanate thin films

Abstract: An understanding of the pyroelectric coefficient and particularly its relationship with the applied electric field is critical to predicting the device performance for infrared imaging, energy harvesting, and solid-state cooling devices. In this work, we compare direct measurements of the pyroelectric effect under pulsed heating to the indirect extraction of the pyroelectric coefficient from adiabatic hysteresis loops and predictions from Landau-Devonshire theory for PbZr0.52Ti0.48O3 (PZT 52/48) on platinized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…24,25 The coexistence of R-T phases provides more polarization directions and exible domain rotation to the ceramic, which makes it easier to be polarized under an external electric eld. 26,27 Comparing the XRD results of CSed and SPSed samples, it can be found that the sample prepared by SPS contains higher content of T phase, due to the value of I(002)/I(200) of the T phase between 44 and 46 is 1 : 2, and the peak of the SPSed samples is closer to 1 : 2 here. [28][29][30] In addition, as shown in Fig.…”
Section: Methodsmentioning
confidence: 89%
“…24,25 The coexistence of R-T phases provides more polarization directions and exible domain rotation to the ceramic, which makes it easier to be polarized under an external electric eld. 26,27 Comparing the XRD results of CSed and SPSed samples, it can be found that the sample prepared by SPS contains higher content of T phase, due to the value of I(002)/I(200) of the T phase between 44 and 46 is 1 : 2, and the peak of the SPSed samples is closer to 1 : 2 here. [28][29][30] In addition, as shown in Fig.…”
Section: Methodsmentioning
confidence: 89%
“…First, suitable measurements of the pyroelectric coefficient ( ∂P / ∂T ) E are necessary . For example, violation of the isostress and isofield conditions, especially in the case of thin films clamped to a substrate, may result in non‐intrinsic contributions to the pyroelectric effect and in extremely large deviation between measured electrocaloric and pyroelectric coefficients …”
Section: Discussionmentioning
confidence: 95%
“…[69] Fore xample,v iolation of the isostress and isofield conditions,e specially in the case of thin films clamped to as ubstrate, may result in non-intrinsic contributions to the pyroelectric effect and in extremely large deviation between measured electrocaloric and pyroelectric coefficients. [70] To evaluate (@P/@T) E from experimental measurements, P(T)c urves are usuallye xtracted from P(E)m easurements at different T,a nd are then fitted by ap olynomial of high order (fourth or sixth) within as mall temperature range.I f the resulting P(T)c urves are not smooth enough, for example,b ecause of too large temperature intervals,t his may give rise to large discrepancies,s ee also Ref. [8].T ypically the P(T)c urves for different valueso fE are estimated from the upper branch of the polarization-electric field hysteresis loops measured at different temperatures.T hus,t he possible appearance of the inverse ECE for small fields sampling the lower branch andp ossible field-induceds witching events (Section3.1.1) are not considered.…”
Section: Artifacts Of the Indirect Methodsmentioning
confidence: 99%
“…Increasing the power density of the device often necessitates the application of high electric fields that also tend to dampen first-order transitions. Direct measurements of the PE have also shown a reduction in the PEC at low electric fields for polydomain thin films and that nonintrinsic effects can have the same order of magnitude as intrinsic effects 15,16 . Temperature perturbations change the polar structure/ order not only at a unit-cell level (i.e., the intrinsic response) but also at a mesoscopic level (e.g., domain structures).…”
mentioning
confidence: 98%